A house for Mr. Biswas - Naipaul, V.S. (New Delhi : Penguin Books, 1969)
Mr Biswas is a man who is not naturally rebellious, but in whom rebellion is inspired by the forces of ritual, myth and custom. Though he has married into the family, Mr Biswas remains an outsider and refuses to follow the family in their habitual devotions.
Keywords: Domestic fiction; East Indians